Genotyping and Molecular Characterization of Dermatophytes Isolates Collected from Clinical Samples - Sheikhi Nasrin; Zaker bostanabad saeed; Mirzaahmadi Sina; Naziri sahar (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2017)
Background: Detection  of  dermatophytes  by  microbiological  method  is  sometimes  problematic and  some  atypical  microscopic  or  macroscopic  morphology  are  non-detectable.  Due  to  morphological similarity  and  existing  intermediate  forms  and  variants,  unequivocally  separating  these  dermatophytes is  not  always  straightforward,  and  sampling  appropriate  isolates  for  research  is  often  troublesome.The  aim  of  this  study  was  to  compare  and  evaluate  use  of  sequencing chitin  synthase  1  gene  (CHS1) with  conventional  methods  for  identification  of  dermatophytes  species  and  we researched  the  genetic patterns of samples collected for general phylogenetic analysis. Material and Method: In the primary screening of 250 clinical samples by KOH microscopy method, 64 isolates has been detected as dermatophytes. All samples were cultured and amplified by PCR Method and  positive  PCR  samples  have  been  sequenced.  Clinical  isolates  (64/250)  were  analyzed  by  using sequencing gene CHS1 and genotyped by program DNAMAN and MEGA. Result: The all data were compared with the international database of national center for biotechnology information website. Based on reference sequences of different genotype strains, it was noted that most strains of Trichophyton mentagrophytes were misidentifications of Trichophyton interdigitale. Conclusion: This  research  demonstrated  that  nested  PCR  and  sequencing  can  be  considered  as standard  method  for  the  diagnosis  of  dermatophytosis.  Also  research  gives  a first  result  on  genetic evolution of the Dermatophytes strains distributing in Iran. It may aid in the creation of a national database that will be a valuable support for further studies.